Six Sigma for Electronics Design and Manufacturing - Shina, Sammy G. (McGraw-Hill's AccessEngineering., 2002)
Six Sigma is a customer-based manufacturing approach to realizing fewer defects and thus lowering costs and increasing customer satisfaction. This is a rigorous engineering book detailing the gritty, statistical work involved in making the Six Sigma process work in the electronics industry.